Second trimester uterine artery pulsatility index and chorionicity in twins - Ergin, Rahime Nida; Yayla, Murat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: We aimed to compare the second trimester uterine artery Pulsatility Index (PI) measurement in twin pregnancies according to the chorionicity and determine its effect on twin pregnancy outcome in terms of fetal and birth weight. Methods: All medical records of twin pregnancies, whose fetal screening was done between May 1999 and January 2012, were evaluated retrospectively. All twin pregnancies without detected/suspicious anatomical or genetic fetal anomalies, biochemical abnormalities, and familial genetic diseases were included in the data analyses. Ones with missing PI measurements and ones with undetermined chorion types were excluded from the data analyses. Results: A total of 149 twin pregnancies were evaluated. The percentages of chorion types were diamniotic dichorionic in 89.9% (n=134) and diamniotic monochorionic 10.1% (n=15). Mean age of the mothers was 31.56 ± 4.9 years. Mean gestational week of PI measurement was 20.30 ± 2.23 weeks. Mean birth week was 35.5 ± 2.50 weeks. Mean birth weight was 2405 ±437 grams. Correlation analyses related to PI values and second trimester weight and birth weight parameters didn’t show any statistically significant correlation. Mean maternal age, mean gestational week of PI measurements, mean birth week, mean fetal weights and birth weights were indifferent between chorionicity groups. Comparisons of second trimester PI, second trimester weight and birth weight and related parameters showed no statistically significant between groups. Conclusions: Second trimester uterine artery pulsatility index measurements do not differ between chorionicity types. It has no effect on twin pregnancy outcome in terms of fetal weight and birth weight.